IMPLEMENTASI PROGRAM KELUARGA SADAR GIZI (KADARZI) DI KABUPATEN SEMARANG - Pradana, Yuliardi Agung; Subowo, Ari; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
A family called Kadarzi when has behaved good nutrition is characterized by weighing out the body weight regularly, giving only breast feeding (ASI) to infants frombirth until the age of six months (exclusive ASI), eat variegated, use iodized salt, and drink nutrition supplements as recommended. Decision of the Ministry of Health Republic of Indonesia Number: 747/Menkes/SK/VI/2007 about Operational Guidelines of Family Nutrition Conscious on Alert Village state that the government's target is 80% of families applying Kadarzi behavior. Achievement of Kadarzi in Semarang Regency only reached 29,6% in 2011. Kadarzi implementation from public attitude still very lacking. The main obstacle of Kadarzi implementation is the low public awareness in the exclusive breast feeding. If one of the indicators in the Kadarzi are not met, then a family can not be called as Family Nutrition Conscious. Low public awareness in the exclusive breast feeding caused breastfeeding mothers who still working. The government should be can give shuttle between services of breast feeding for working mother who had baby aged 0-6 months, so exclusive breastfeeding can be met, which Kadarzi also will be achieved later.